Well-being in Rapidly Developing China - Okulicz-Kozaryn, Adam (Zadowolenie z życia w szybko rozwijających się Chinach, 2010)
While China enjoyed unmatched economic growth during last three decades, the question remains whether there is a similar increase in quality of life or well-being. Extant well-being research was mostly done in the developed countries, and few investigations in China are cross-sectional. This paper uses World Values Survey (WVS) to show trend in well-being in China from 1990 to 2007. Paper concludes with a comparison of well-being by socioeconomic groups.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 67-77
Keywords: well-being; life satisfaction; China